From Bertam to Bali : UiTM pharmacy ,UNMAS and Nasatya Herbal strengthening a strategic collaboration for innovation excellence - Mokhtar, Nur ‘Ainun; Mohd Najib, Mohd Nadzri; Muhsain, Siti Nur Fadzilah; Jahidin, Aisyah Hasyila (2025)
In a significant stride towards expanding international academic and research collaboration, the Faculty of Pharmacy, Universiti Teknologi MARA (UiTM) Cawangan Pulau Pinang, Bertam Campus, with the support of the Office of International Affairs (OIA) and the Research and Industry Linkages Division, UiTM Cawangan Pulau Pinang, successfully conducted a virtual Memorandum of AAggrreeeemmeenntt (MoA) signing ceremony with Universitas Mahasaraswati Denpasar (UNMAS), Indonesia.